The Russian invasion of Ukraine and its impact on digitalized small firms in Central and West Asia: Evidence from rapid surveys - Shigehiro Shinozaki (Asian Development Bank Institute (ADBI), 2023)
The Russian invasion of Ukraine disrupted a V-shaped economic post-pandemic recovery in Central and West Asia. It affected global supply chains and slowed the region's growth momentum while adding inflationary pressures. Private businesses were adversely affected by the impact of the invasion and global sanctions against the Russian Federation, with the effects being more pronounced for micro- and small firms. As the pandemic helped create a base of digitalized firms, this paper discusses how business digitalization-and the use of digital finance-affected the operations of small firms as the impact of the invasion began to be felt. It uses a linear probability regression based on rapid business surveys conducted in seven Central and West Asian countries-Armenia, Azerbaijan, Georgia, Kazakhstan, the Kyrgyz Republic, Tajikistan, and Uzbekistan. The results show that digitalization has yet to allow small firms to take full advantage of the opportunities it offers for more efficient business operations. Digital finance has yet to be well accepted and used by small businesses, even those already digitalized. Micro- and small firms already digitalized can be split into two groups: those maximizing business opportunities and those suffering from global sanctions. Based on the analysis, the paper suggests four policy implications that can help promote business digitalization of small firms across the region.
Keywords: D22; G20; L20; L50; 330; Russian invasion of Ukraine; digitalization; digital financial services; access to finance; SME development; SME policy; Central and West Asia